In fair value we trust, or not - TANG, Joyce (Institutional Knowledge at Singapore Management University, 2016)
The objective of financial reporting is to provide financial information that is useful to existing and potential investors, lenders and other creditors (IASB’s Conceptual Framework ED/2015/3). General purpose financial reports provide information about the financial position of a reporting entity, as well as information about the effects of transactions and other events that will change a reporting entity’s economic resources and claims (para 1.12 ED/2015/3). Investor confidence and trust in the financial statements is a crucial component for financial markets to function smoothly. This report presents the attitudes and concerns of over 700 respondents toward fair value accounting. The survey shows there is a high level of trust toward financial statements, with higher levels of trust shown in financial statements prepared using a hybrid measurement model of historical cost and fair value accounting vis-à-vis a single measurement basis model (either historical cost or fair value accounting).More than 75% of the survey respondents perceive fair value accounting to provide useful information for trading securities, available-for-sale securities and real estate; but less than 60% of the respondents perceive fair value accounting to provide useful information for held-to-maturity securities, loans and receivables, property, plant and equipment, biological assets and intangible assets. However, there are lingering concerns toward the reliability of fair value measurements. Specifically, 26% of respondents state that they distrust fair value estimates. The survey respondents have low/very low trust in Level 3 fair value estimates (39%) as compared to Level 1 and Level 2 fair value estimates (13% and 23% respectively).